2008
DOI: 10.1371/journal.ppat.1000097
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Ecology and Natural History of Simian Foamy Virus Infection in Wild-Living Chimpanzees

Abstract: Identifying microbial pathogens with zoonotic potential in wild-living primates can be important to human health, as evidenced by human immunodeficiency viruses types 1 and 2 (HIV-1 and HIV-2) and Ebola virus. Simian foamy viruses (SFVs) are ancient retroviruses that infect Old and New World monkeys and apes. Although not known to cause disease, these viruses are of public health interest because they have the potential to infect humans and thus provide a more general indication of zoonotic exposure risks. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
164
5
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(186 citation statements)
references
References 77 publications
(160 reference statements)
15
164
5
2
Order By: Relevance
“…However, no clustering according to the geographic origin of the chimpanzees was found. The comparison of the strains described here with recently published SFV strains from wild P. t. schweinfurthii from Uganda, Congo and Tanzania [4] could also not identify clustering by geographical origin. These results are consistent with previous findings [4] which could not show region-specific clusters of SFV strains within one chimpanzee subspecies.…”
Section: X83298 Ay686179 Ay583781contrasting
confidence: 60%
See 3 more Smart Citations
“…However, no clustering according to the geographic origin of the chimpanzees was found. The comparison of the strains described here with recently published SFV strains from wild P. t. schweinfurthii from Uganda, Congo and Tanzania [4] could also not identify clustering by geographical origin. These results are consistent with previous findings [4] which could not show region-specific clusters of SFV strains within one chimpanzee subspecies.…”
Section: X83298 Ay686179 Ay583781contrasting
confidence: 60%
“…The comparison of the strains described here with recently published SFV strains from wild P. t. schweinfurthii from Uganda, Congo and Tanzania [4] could also not identify clustering by geographical origin. These results are consistent with previous findings [4] which could not show region-specific clusters of SFV strains within one chimpanzee subspecies. However, this study shows in principle the possibility of pathogen introduction to great ape communities in sanctuaries which can cause co-infections with multiple virus strains.…”
Section: X83298 Ay686179 Ay583781contrasting
confidence: 60%
See 2 more Smart Citations
“…When Hahn's group looked for evidence of foamy virus infection in wild equatorial African chimpanzees by testing for antibody and nucleic acid in fecal samples, they confirmed a prevalence of between 44 and 100%. 2 Morozov et al 3 found that 12 of 14 free living chimpanzees in Tai National Park (Cô te d'Ivoir) were Semliki forest virus (SFV) infected. The sensitive assays used by Jones-Engel et al 4 found, not only that more than 92% of wild non-human primates were SFV positive in Thailand but that some had already been seroconverted by the age of 3.…”
Section: Foamy Virus Infection In Animals and Humans Does Not Cause Dmentioning
confidence: 99%